Developing a Generative AI-Assisted Training Module for Integrated Digital Big Book in Guidance and Counseling to Enhance Elementary Teachers’ Pedagogical Competence - Chrisma Prateila Kusumaningsih; Yari Dwikurnaningsih; Stefanus Christian Relmasira (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2026)
This study aims to develop and evaluate the effectiveness of a Generative AI-based training module in enhancing the pedagogical competence of elementary school teachers, particularly in integrating Guidance and Counseling (BK) services into daily instructional practices. The study involved a sample of 72 elementary school teachers drawn from six schools within a single educational cluster. The participants were selected using a cluster random sampling technique, ensuring that each school had an equal probability of being assigned to either the experimental or control group. The findings indicate that the Generative AI-based training module significantly improved teachers’ pedagogical competence, as evidenced by an average N-Gain score of 73.28%. The module effectively enhanced teachers’ conceptual understanding and practical ability to integrate BK services into classroom instruction, while simultaneously promoting a pedagogical approach that fosters students’ character development and socio-emotional competencies. This study concludes that the integration of AI in education, particularly through the development of Digital Big Book media, not only enriches instructional content but also reinforces essential social and ethical values required in 21st-century learning environments. Furthermore, the study recommends extending future research to a broader range of schools and investigating specific AI tools to examine the long-term impact, scalability, and sustainability of the competencies acquired by teachers.